A BERT-based rice enhancer identification model combined with sequence-representation differential entropy interpretation - Pu, Yajing; Hao, Xintong; Zheng, Zhaoqi; Ma, Huiyan; Lv, Zhibin (Frontiers in Plant Science, 2025)
Rice is a crucial food crop, and research into its gene expression regulation holds significant importance for molecular breeding and yield improvement. Enhancers, as key elements regulating the spatiotemporal-specific expression of genes, represent a core challenge in functional genomics due to their precise identification requirements. Current deep learning-based methods for rice enhancer identification face limitations primarily in feature extraction efficiency and the generalization capabilities of model architectures. In response, this study introduces a novel model architecture, RiceEN-BERT-SVM, which integrates DNABERT-2 as a feature extraction tool, alongside Support Vector Machine (SVM) for enhancer sequence classification. The mechanism underlying the optimization of model performance is elucidated through differential entropy analysis of feature representations. Experimental results demonstrate the high precision of this approach, achieving an accuracy of 88.05% in 5-fold cross-validation and 87.55% in independent testing. These metrics surpass current state-of-the-art (SOTA) models by margins ranging from 1.47% to 6.87% on the same dataset. Further refinement through fine-tuning enhances RiceEN-BERT-SVM's performance, increasing its accuracy by an additional 6.95%, resulting in a final accuracy of 93.63%. The study employs differential entropy analysis of sequence feature representations to explain the performance enhancements observed with increased fine-tuning iterations. As the number of iterations rises, the differential entropy distributions of positive and negative sample features gradually separate from their initial overlapping state, corresponding with the model's progressive improvement in performance. At six fine-tuning iterations, the separation between positive and negative sample entropy reaches its peak, achieving optimal model performance. Beyond this point, the distributions begin to overlap again, leading to a decline in performance. This novel approach not only offers an efficient tool for rice enhancer identification but also introduces a visually interpretable framework based on differential entropy, providing a new perspective for optimizing biological sequence analysis models.